GEMATI Program: Reducing the Incidence of Stunting - Arif Rakhman; Khodijah; Ita Nur Itsna; Oktiawati, Anisa (Jurnal Berita Ilmu Keperawatan, 2025)
Chronic malnutrition can cause growth and development disorders in children. This case is named stunting. Stunting is often experienced by toddlers in Indonesia. One of the main concerns of Tegal Regency Government is the high incidence of stunting. Efforts to decrease the incidence of stunting with structured interventions involving the community, especially parents who have children below two years of age. The study aimed to assess the efficacy of the Gemati program, namely the community assistance movement in Tegal Regency. The study took a quantitative approach and used a pre-experimental design with a single-group pretest-posttest design. All of the respondents were mothers of toddlers who were small in height. The sampling method was a total sampling. The study’s findings revealed an improvement in toddler mothers’ knowledge and skills in detecting and preparing a balanced nutritional menu. The government and the community must collaborate to ensure that the stunting prevention program is carried out effectively in order to reduce stunting. The government determines the policies to control stunting and protect the rights of mothers and children, increasing food security and environmental sanitation, and giving health education about stunting continually. The Gemati program has to be implemented sustainably and applied to all villages that have a high incidence of stunting so that the acceleration of handling stunting in Tegal Regency can achieve the results optimally.